Motion Graphic Sebagai Media Edukasi Cybercrime di Kalangan Mahasiswa - Selly Artaty Zega; Samuel Butar- Butar; Nelmiawati Nelmiawati (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2023)
Cybercrime is crime using the internet network, this crime can be snared by anyone, one of them is Informatics Engineering Students, the author has distributed questionnaires, to obtain data on victims of cybercrime crimes for Informatics Engineering Students, data obtained that victims of cybercrime crimes are higher than those who are not ensnared become victims of cybercrime, this happens because of the lack of information obtained by students.Motion graphics are used as a medium to provide education to Informatics Engineering students regarding cybercrime crimes, these media are used because they can display videos with a visual text, images, and audio that are interesting and easy to understand.The research method used is Research And Development (RND), with the product development method, namely Villamil Molina, using quantitative descriptive analysis, through alpha testing with the interview method to motion graphic media experts and beta testing with the Likert scale measurement method to Informatics Engineering Students. This research produced a motion graphic video with a duration of 5 minutes 12 seconds in mp4 format, and obtained the results of a product feasibility analysis with a percentage of 86% and categorized as very feasible.